Diplomacy, Roger Makins and the Anglo-American relationship - Wevill, Richard (Ashgate Publishing Limited, 2014)
Roger Makins, British Ambassador to Washington 1953-1956, was one of the most prominent and powerful diplomats of his time. His career was unusual for a Foreign Office official, in that such a large part of it took place in Washington and London, and was centered on Anglo-American relationships. This book describes his life, times and the important players he dealt with on both sides of the Atlantic. It sheds light on how the 'special relationship' between Britain and America developed, and shows how great an impact a civil servant can have on policy.